(untitled) (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Withaningsih S, Parikesit, Iskandar J, Putri R. 2019. Socio-ecological perspective of local bio-resources based production system of palm sugar and palm flour from aren (Arenga pinnata): Case study of Sukaresmi Village, West Bandung, Indonesia. Biodiversitas. 20: 1990-1997. The heterogeneity of landscapes, from a socio-ecology viewpoint, has resulted in the emergence of various systems of production for the same end products, which have developed with wide variations and distinctiveness and are based on the local availability of bio-resources. Even on landscapes with extreme biophysical and social conditions, various systems of production can still be encountered. Bio-resource-based systems generally exist on a small scale and in poorly-resourced communities. This study aimed to determine the use of local bio-resources and palm management techniques in different systems used for the production of palm sugar and palm flour. This study utilized a combination of qualitative and quantitative methods. Primary data were collected using structured and semi-structured interviews, observations, and participants’ observations. The results showed that palm sugar was processed by peeling the midrib, passing, tapping, and making the midrib into sugar, whereas palm flour was processed by cutting down trees, grating, squeezing, and precipitating the end product. The local bio-resources used in the production of both included Chinese albizia (Albizia chinensis), giant bamboo (Dendrocalamus giganteus), tali bamboo (Gigantochloa apus), kemang (Mangifera kemanga), jackfruit (Artocarpus heterophyllus), and sobsi (Maesopsis eminii). Local knowledge regarding the processing of palm sugar was passed from generation to generation, whereas the knowledge regarding the processing of palm flour was achieved through independent learning and asking questions.